An Ordinance to Prevent the Use of Fire Arms, § 1, in Charter of the City of Hudson 109 (1868) - (:unkn) unknown (My University, 1855)
1: No person shall within this city carry any gun on lands not his own, without the written permission of the owner of legal possessor of such lands.
Keywords: CARRY